Ensayos no destructivos como herramienta para el dimensionamiento de discontinuidades en la superficie externa de tuberías (2010)
In petrochemical industry, it is necessary to use a Non-destructive testing that allows, in a fast and suitable way, the quantification of the present corrosion on the external surface of the pipes used by oil pipelines and gas pipelines. Currently, this process is executed manually, making it slow and tedious to obtain the results and subject to human error. Therefore, in this paper the study of the main Non-destructive testing is done to choose the most suitable one, so that it allows extracting information from the corroded zones, such as: the maximum depth of the corroded area and the projection of this on the longitudinal axis of the pipelines. This information is required for the analysis of the integrity and determination of the maximum pressure of the pipelines operation, according to the regulations established for transport and distribution of the hydrocarbon, in particular the ASME B31G code.